INCIDENCE, MANAGEMENT AND SUBSEQUENT OUTCOME OF TRANSCATHETER EMBOLIZED DEVICES- THREE YEARS AUDIT AT A TERTIARY CARDIAC CARE CENTER - Akhtar, Khurram; Ullah, Maad; Sadiq, Nadeem; Sultan, Mehbood; Akbar, Hajra (Pakistan Armed Forces Medical Journal, 2021)
Objective: To audit the incidence of misplaced devices during varied interventional procedures carried out in our catheter lab over a period of three years. Study Design: Descriptive study Place and Duration of Study: Armed Forces Institute of Cardiology & National Institute of Heart Diseases. From January 2011 to December 2103 Material and Methods: All adult and pediatric cases with structural heart disease both congenital and acquired undergoing interventional procedures were included in the study. Out of a total of 3256 patients, 1174 patients who underwent cardiac catheter device implantation procedures during the study period were included in the study. Results: Nineteen patients out of 1174 patients (1.6%) had device embolization acutely or sub acutely following the procedure. The varied reasons for the device embolizations were analyzed in this study. Conclusion: We concluded that for retrieval to be successful via the transcathter approach, it was important to have a wide selection of retrieval equipment available and to be conversant with its use. Our audit also concludes that device implantation at our center are safe and an effective procedure with minimal complications.